2012
DOI: 10.1111/chf.12004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Tricuspid Valve Annuloplasty in Addition to Mitral Valve Surgery

Abstract: ©2012 Wiley Periodicals, inc. Current guidelines recommend tricuspid valve annuloplasty (TVP) together with mitral valve surgery in cases of tricuspid annulus dilation (≥40 mm) or functional tricuspid valve regurgitation >2/4. Baseline clinical and echocardiographic data of patients undergoing mitral valve surgery in a single tertiary care hospital between 2007 and 2010 were analyzed. Mortality and heart failure hospitalization data were collected and groups with or without TVP were compared. Patients with TVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…These data were adjusted for LV parameters, as possible confounders of outcome. Opposed to this, several studies failed to show that TA is beneficial in patients with other causes of MR 16 17. Especially in degenerative mitral valve disease, the value of TA is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data were adjusted for LV parameters, as possible confounders of outcome. Opposed to this, several studies failed to show that TA is beneficial in patients with other causes of MR 16 17. Especially in degenerative mitral valve disease, the value of TA is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the outcome in patients undergoing MVS with or without TA is notoriously difficult because the former often present in a worse clinical state with more severe TR, higher New York Heart Association (NYHA) functional class and decreased RV function 3. Cross-sectional studies therefore failed to show improved outcome for patients undergoing simultaneous TA and MVS in the past 16 17…”
Section: Introductionmentioning
confidence: 99%
“…As well as mortality, a prior study [33] and our recent data [34] demonstrated that the risk of heart failure that requires admission following TA is as high as 40%. The present result that includes a large cohort of patients who underwent TA, confirms that heart failure is common and constitutes the majority of MACE (67%).…”
Section: Discussionmentioning
confidence: 88%
“…After exclusion of duplicate or irrelevant references, 114 potentially relevant articles were retrieved. After application of the inclusion and exclusion criteria, 31 relevant articles were included in the study 5,12,21‐49 : randomized trials ( n = 3), 24,42,45 propensity score‐adjusted ( n = 4), 12,26,31,46 and observational non‐adjusted ( n = 24) 5,20‐22,24,26‐29,31‐43,45‐48 …”
Section: Resultsmentioning
confidence: 99%
“…After application of the inclusion and exclusion criteria, 31 relevant articles were included in the study 5,12, : randomized trials (n = 3), 24,42,45 propensity score-adjusted (n = 4), 12,26,31,46 and observational non-adjusted (n = 24). 5,[20][21][22]24,[26][27][28][29][31][32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48] A total of 9663 patients were included for analysis. Among them, the funnel plots did not show significant asymmetry to suggest publication bias with outcomes selected (Figure S2).…”
Section: Literature Searchmentioning
confidence: 99%